Digital Romance: Self-Presentation Strategies of Jakarta's Dating App Users - Kenny, Kenny; Puspita, Virienia; Ramadhani W, Filzah; Sedharta, Benedict Owen (Journal La Sociale, 2025)
In the rapidly evolving digital age, self-presentation has become an integral part of human interaction, particularly in the realm of digital romance through modern dating applications. This study analyzes the digital self-presentation strategies of users of Tinder, Bumble, and Coffee Meets Bagel in Jakarta. Using a qualitative descriptive method and Erving Goffman's self-presentation theory, data were collected through profile observations and interviews with 15 informants aged 23 to 33 who have used these apps for over a year. The findings identify several self-presentation strategies used by dating app users. Both male and female users take selfies with various poses to create natural-looking images. For instance, Bumble users use clear facial photos in formal attire to give a professional impression, while informant DA shows a neat and serious appearance in professional settings. Bumble users also use polite and open language with detailed writing styles. Coffee Meets Bagel users, such as informants display photos in formal attire and emphasize emotional intelligence in their profiles. Tinder users’ informants like to highlight their dedication to fitness and use casual language with humor to create a pleasant impression. The study reveals strategies like self-disclosure, authenticity, subtle cues, and the importance of valid self-presentation in digital romance.